Communication rights in the south american constitutions interface between's the urge and the recognition of rights related to communication - Xavier, Renan Schlup [UNESP] (Univ Federal Sergipe, 2015)
This article aims to articulate the relationship between the urge of communication rights, established from global or regional movements that underlie them, and the recognition through the constitutional positivization. At first, it identifies the urge of the rights movements and then identifies which rights are urged to every movement, defining a trajectory for the rights. Then, the constitutions of the states are analyzed. As a general goal, the identification of constitutional maturity of each country regarding the communication field.
Keywords: Communication Policies; Latin America; Constitution; Communication Rights